Microbial melatonin metabolism in the human intestine as a therapeutic target for dysbiosis and rhythm disorders - Petra Zimmermann; Salome Kurth; Benoit Pugin; Nicholas A. Bokulich (npj Biofilms and Microbiomes)
Abstract Melatonin (MT) (N-acetyl-5-methoxytryptamine) is an indoleamine recognized primarily for its crucial role in regulating sleep through circadian rhythm modulation in humans and animals. Beyond its association with the pineal gland, it is synthesized in various tissues, functioning as a hormone, tissue factor, autocoid, paracoid, and antioxidant, impacting multiple organ systems, including the gut-brain axis. However, the mechanisms of extra-pineal MT production and its role in microbiota-host interactions remain less understood. This review provides a comprehensive overview of MT, including its production, actions sites, metabolic pathways, and implications for human health. The gastrointestinal tract is highlighted as an additional source of MT, with an examination of its effects on the intestinal microbiota. This review explores whether the microbiota contributes to MT in the intestine, its relationship to food intake, and the implications for human health. Due to its impacts on the intestinal microbiota, MT may be a valuable therapeutic agent for various dysbiosis-associated conditions. Moreover, due to its influence on intestinal MT levels, the microbiota may be a possible therapeutic target for treating health disorders related to circadian rhythm dysregulation.